A quality improvement intervention to reduce emergency department radiography for bronchiolitis. (April 2018) - Reiter, Joel; Breuer, Adin; Breuer, Oded; Hashavya, Saar; Rekhtman, David; Kerem, Eitan; Cohen-Cymberknoh, Malena
Abstract: Introduction: Bronchiolitis is one of the most common infectious diseases in children and the most frequent cause of hospitalization in infants. Clinical practice guidelines recommend that a chest X-ray (CXR) should not be routinely obtained in the diagnosis of bronchiolitis, as studies have shown that they do not affect clinical outcomes, but rather lead to overuse of pharmacological agents and a longer length of hospital stay. Objective: To determine whether active institution of bronchiolitis practice guidelines as part of a quality improvement project decreased the use of CXRs in the Pediatric Emergency Department (ED). Secondary outcomes included a decrease in the use of unnecessary medical interventions and a shorter mean hospital length of stay. Methods: The study was conducted at two Hadassah Medical Center Pediatric EDs. Guidelines were reviewed with the ED staff during departmental seminars by a senior pediatric pulmonologist, and posted at the physician computer stations in the ED. Prospective, post-intervention, data obtained during the study period was compared to retrospective, pre-intervention, data from the year prior to implementation of the intervention. Results: Post-intervention, 37% of patients vs. 58% in the retrospective cohort had a CXR via ED referral (p < 0.001). The use of hypertonic saline and bronchodilators decreased, while there was no significant change in antibiotic or corticosteroid use. There was a decrease in hospitalizations post-intervention (70% vs. 77%, p = 0.05). Conclusion: This key intervention was successful in reinforcing the AAP guidelines, promoting greater cost-effectiveness, reducing radiation exposure, and saving valuable time and resources for the ED staff and the hospital. Highlights: A simple, successful intervention targeting chest radiography in bronchiolitis. Chest radiography decreased by 44% to a post-intervention rate of 36.6%. Following the intervention, hospitalizations decreased by 10%. When performed, chest X-rays yielded more clinically significant findings.